2006
DOI: 10.1345/aph.1h028
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diarrhea at a University Hospital and Association with Modifiable Risk Factors

Abstract: Diarrhea was prevalent in 12.4% of hospitalized patients at a large university hospital at one point in time. Patients with diarrhea were more likely to have CD infection, receive antibiotics, or experience a longer hospitalization. Half of the CD diarrhea cases occurring in the hospital had been previously unidentified. Hospitalized patients should be evaluated for diarrhea on an ongoing basis with appropriate interventions instituted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 11 publications
1
30
0
1
Order By: Relevance
“…Although our hospital uses the cell cytotoxicity assay, considered the most sensitive diagnostic test, our rates represent testing based on clinical suspicion of CDI. We have previously shown that up to half of patients with CDI do not get tested for CDI without active surveillance [26]. Thus, the rates observed in this paper may be falsely low due to false negative test results, non-testing of infected patients, or both.…”
Section: Discussionmentioning
confidence: 63%
“…Although our hospital uses the cell cytotoxicity assay, considered the most sensitive diagnostic test, our rates represent testing based on clinical suspicion of CDI. We have previously shown that up to half of patients with CDI do not get tested for CDI without active surveillance [26]. Thus, the rates observed in this paper may be falsely low due to false negative test results, non-testing of infected patients, or both.…”
Section: Discussionmentioning
confidence: 63%
“…We have recorded those variables reported as main confounders for the development of diarrhoea in hospitalised patients (age, illness severity, antibiotic administration, low serum albumin and admission in the summer months). Furthermore, other demographic and clinical variables were recorded for each patient (gender, LOS, NIHSS score at admission as measure for stroke severity).…”
Section: Methodsmentioning
confidence: 99%
“…These tests are more sensitive for C. difficile in toxinsamples, but may be less specific for CDI (Wilcox et al 2010; Dubberke et al 2011; Kufelnicka and Kirn 2011). For example, if 20% of hospitalized patients are colonized with C. difficile (Viscidi et al 1981; McFarland et al 1989; Samore et al 1994; Kyne et al 2000; Cohen et al 2010) and most nosocomial diarrhea is unrelated to CDI (McFarland 1995); Bartlett 2002; Garey et al 2006; Yadav et al 2009), it seems likely that some patients with diarrhea and C. difficile are carriers with diarrhea due to other causes (Wilcox et al 2010; Kufelnicka and Kirn 2011). Thus, toxin tests may miss occasional patients with CDI while direct tests for C. difficile may result in overdiagnosis and overtreatment.…”
Section: Introductionmentioning
confidence: 99%